Rocket launcher: A novel reduction technique for posterior hip dislocations and review of current literature. (6th April 2015) - Dan, Michael; Phillips, Alfred; Simonian, Marcus; Flannagan, Scott
Abstract Objective We provide a review of literature on reduction techniques for posterior hip dislocations and present our experience with a novel technique for the reduction of acute posterior hip dislocations in the ED, 'the rocket launcher' technique. Methods We present our results with six patients with prosthetic posterior hip dislocation treated in our rural ED. We recorded patient demographics. The technique involves placing the patient's knee over the shoulder, and holding the lower leg like a 'Rocket Launcher' allow the physician's shoulder to work as a fulcrum, in an ergonomically friendly manner for the reducer. We used Fisher's t‐test for cohort analysis between reduction techniques. Results Of our patients, the mean age was 74 years (range 66 to 85 years). We had a 83% success rate. The one patient who the 'rocket launcher' failed in, was a hemi‐arthroplasty patient who also failed all other closed techniques and needed open reduction. When compared with Allis (62% success rate), Whistler (60% success rate) and Captain Morgan (92% success rate) techniques, there was no statistically significant difference in the successfulness of the reduction techniques. There were no neurovascular or periprosthetic complications. Conclusion We have described a reduction technique for posterior hip dislocations. Placing the patient's knee over the shoulder, and holding the lower leg like a 'Rocket Launcher' allow the physician's shoulder to work as a fulcrum, thus mechanically and ergonomically superior to standard techniques.